Mediation of Organizational Commitment on the Influence of Motivation and Skills on Employee Performance - Tri Sinarti; Thusy Tiara Saraswati (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2022)
This study aims to analyze the mediating variable Organizational Commitment on the influence of motivation and skills on the employee performance of Tulung Agung marble centre, East Java. The population in this study were employees totalling 1.500 employees, and samples were taken using a random sampling method using the Slovin formula, namely 93 employees. The goal to be achieved is to see the significance of the influence of motivation and skills variables directly on employee performance and indirectly by mediating organizational commitment at the Tulungagung marble business centre, East Java. The data source in this study is primary data taken directly from employees by distributing a list of questions related to Motivation, Skills, Organizational Commitment and Employee Performance. Respondents' answer scale using a Likert scale. The analysis technique used is Smart PLS analysis. The research results show that there is a motivational influence on organizational commitment. There is no effect of skills on organizational commitment. There is no effect of motivation and skills on employee performance. There is an influence of organizational commitment on employee performance. There is an indirect effect of motivation on employee performance through organizational commitment. There is no indirect effect of skills on employee performance through organizational commitment.